Utility of color Doppler in diagnosing ureteric calculi: a useful adjunct - Ravinder Sahdev; Akhilesh Rao; Neha Yadu; Y Shukla (International Journal of Medical Research and Review, 2016)
Background: Renal colic is a common presenting complaint in patients report to the out patient department. Usually the first investigation these patients undergo is ultrasound because of its widespread availability. Using color Doppler to study the characteristics of urine jet emanating from the vesicoureteric junction might prove useful in improving the diagnostic accuracy of ultrasound in patients with suspected ureteric calculi.Methods: All patients found to have unilateral ureteric calculi on non-enhanced computerized tomography between March 2015 to August 2016 were subject to sonographic assessment. Color Doppler interrogation was done to study the ureterovesical jet characteristics. The cut-off values for differences between obstructed and unobstructed side were calculated on the basis of Receiver Operating Characteristic (ROC) curve.Results: A total of 67 patients conforming to our inclusion criteria were selected for the study. There were significant differences of jet frequency (P < 0.05), duration (P < 0.05) and peak velocity (P < 0.05) between obstructed and non-obstructed ureters. The cut-off values for these parameters based on our study population for ureterovesical jet frequency, uration and peak velocity were <1 jet per minute, <2.5 seconds and <7 cm/sec respectively. The combined sensitivity and specificity of these three parameters was calculated as 99.45% and of 99.99% respectively.Conclusion: Flow dynamics studies of ureterovesical jet characteristics using color Doppler significantly increase the sensitivity and specificity of ultrasound for diagnosis of ureteric obstruction. It may be incorporated as an adjunct to gray-scale ultrasound in routine practice to improve accuracy.